2020
DOI: 10.1017/s2040174420001129
|View full text |Cite
|
Sign up to set email alerts
|

Reduced peanut sensitization with maternal peanut consumption and early peanut introduction while breastfeeding

Abstract: New guidelines for peanut allergy prevention in high-risk infants recommend introducing peanut during infancy but do not address breastfeeding or maternal peanut consumption. We assessed the independent and combined association of these factors with peanut sensitization in the general population CHILD birth cohort (N = 2759 mother–child dyads). Mothers reported peanut consumption during pregnancy, timing of first infant peanut consumption, and length of breastfeeding duration. Child peanut sensitization was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…In agreement with these peanut outcome findings, the CHILD birth cohort observational study, found a reduced risk of peanut sensitization if mothers introduced peanut early while breastfeeding and regularly consumed peanut themselves (0.3% sensitization; aOR 0.07, 0.01-0.25). 8 However, our egg allergy (but not egg sensitization) results appear to potentially favor lower maternal egg consumption during breastfeeding to reduce infant egg allergy. Hence, maternal consumption levels of different food allergens may lead to allergen-specific infant outcomes, which requires further investigation in larger future trials.…”
Section: Discussionmentioning
confidence: 72%
“…In agreement with these peanut outcome findings, the CHILD birth cohort observational study, found a reduced risk of peanut sensitization if mothers introduced peanut early while breastfeeding and regularly consumed peanut themselves (0.3% sensitization; aOR 0.07, 0.01-0.25). 8 However, our egg allergy (but not egg sensitization) results appear to potentially favor lower maternal egg consumption during breastfeeding to reduce infant egg allergy. Hence, maternal consumption levels of different food allergens may lead to allergen-specific infant outcomes, which requires further investigation in larger future trials.…”
Section: Discussionmentioning
confidence: 72%
“…Allergens bound to IgG have been shown to induce more Tregs and more profound immune tolerance than free allergens [46], suggesting that exposure to IgG-complexed food antigens through breastmilk may contribute to food allergy prevention [47]. This hypothesis is supported by recent data from the CHILD Cohort Study, where infants who were introduced to peanut before weaning and breastfed by mothers who regularly consumed peanuts had a reduced risk of peanut sensitization and allergy through 5 years of age [48 ▪ ].…”
Section: Maternal Milk and Mucosal Immunitymentioning
confidence: 88%
“…Although some differences exist between different guidelines (Table 2), they all recommend not delaying the introduction of allergenic foods beyond 6–12 months. The remaining questions include the dose, frequency and duration required to achieve oral tolerance induction, the role of maternal dietary exposure (or the triple exposure hypothesis), what adjuncts may help with avoiding Th2 skewing (vitamin D, immunization) and the role of other environmental (e.g., detergents, pollution) and nutritional factors 60–65 …”
Section: An Ounce Of Prevention Is Worth a Pound Of Curementioning
confidence: 99%